Wireless body area network revisited - Taha, Mustafa Sabah; Rahim, Mohd Shafry Mohd; Hashim, Mohammed Mahdi; Johi, Fadil Abass (International Journal of Engineering and Technology, 2026)
Rapid growth of wireless body area networks (WBANs) technology allowed the fast and secured acquisition as well as exchange of vast amount of data information in diversified fields. WBANs intend to simplify and improve the speed, accuracy, and reliability of communica-tions from sensors (interior motors) placed on and/or close to the human body, reducing the healthcare cost remarkably. However, the secu-rity of sensitive data transfer using WBANs and subsequent protection from adversaries attack is a major issue. Depending on the types of applications, small and high sensitive sensors having several nodes obtained from invasive/non-invasive micro- and nano- technology can be installed on the human body to capture useful information. Lately, the use of micro-electro-mechanical systems (MEMS) and integrated circuits in wireless communications (WCs) became widespread because of their low-power operation, intelligence, accuracy, and miniaturi-zation. IEEE 802.15.6 and 802.15.4j standards have already been set to specifically regulate the medical networks and WBANs. In this view, present communication provides an all-inclusive overview of the past development, recent progress, challenges and future trends of security technology related to WBANs.